UJI MUTU FISIK DAN FISIOLOGIS BENIH POHON PENGHASIL GAHARU (Aquilaria microcarpa Baill.) BERDASARKAN FENOTIPE POHON INDUK DI KHDTK SAMBOJA KABUPATEN KUTAI KARTANEGARA - Mira Kumala Ningsih; Maya Preva Biantary; Jumani Jumani (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
Physical and physiological quality test of eaglewood tree (Aquilaria microcarpa Baill.) seeds based on mother tree phenotype from KHDTK Samboja, Kutai Kartanegara Regency.The objective of this research was to find out mother tree phenotype of Aquilaria microcarpa Baill. species in KHDTK Samboja, to find out seed physical quality (moisture content, 1000 seeds weight and range of seeds purity), seed physiological quality (seeds viability and vigor),  and to find out the relationship between both quality with the mother tree phenotype in KHDTK Samboja.  There were four mother tree from Aquilaria microcarpa Baill. species in KHDTK Samboja that bear fruit.  Each mother tree numbered with SBJ 01, SBJ 02, SBJ 03 and SBJ 04.  The results of observation to mother tree/stands phenotype was tree number SBJ 02 had the highest score and SBJ 03 had the lowest score.  The highest score tend to have more eaglewood content and lowest score had little eaglewood content.  But overall the trees grow well and did not show disturbance in growth.Physical quality test was conducted in laboratory of BPTKSDA Samboja, whereas physiological quality test was conducted in green house of BPTKSDA Samboja.  This research was conducted during nine weeks from March until May 2014.  The test procedure was adapted from Thomsen dan Diklev (2004) and refer to International Seed Testing Association (ISTA).  The data of each viability and vigor was analyzed by analysis of variance (anova). The result shows that seeds of A. microcarpa that collected from 4 (four) mother tree in KHDTK Samboja included in recalcitrant seed with moisture content between 33,45% until 52,48%. Recalcitrant seed was seeds that could not stored in longer time.  According to the result of data analyze ascertainable that percentage of seed purity between 64,3 % until 90,5 % with average of 1000 seeds weight was 37,0102 with renge between 32,3984 hingga 44,1686 grams.The result of multiple range test LSD shows that seeds from mother tree 4 had the best physiological quality with seeds viability as 64% and seeds vigor as 75,5% at confidence level 95%. Seeds physical and physiological quality was closely related to genetics factor, growth and environment.  Seeds physical and physiological quality that resulted was inversely proportional with eaglewood potential, in other words seeds mother tree that had the highest score will result small vigor.